APPLICATION OF GROUP COUNSELING USING SOCIODRAMA TECHNIQUES TO IMPROVE COMMUNICATION SKILLS IN CLASS V STUDENTS OF AL-USWAH INTEGRATED ISLAMIC PRIMARY SCHOOL IN BANYUWANGI: PENERAPAN BIMBINGAN KELOMPOK DENGAN TEKNIK SOSIODRAMA UNTUK MENINGKATKAN KETERAMPILAN KOMUNIKASI PADA SISWA KELAS V SEKOLAH DASAR ISLAM TERPADU AL-USWAH DI BANYUWANGI - Neni Rosida Neni Rosida; Heriberthus Wicaksono; Ratna Wulandari (Program Studi Bimbingan dan Konseling, 2023)
This research was carried out at the Al-Uswah Banyuwangi Integrated Islamic Elementary School. To find out whether sociodrama techniques are effective in improving students' communication skills. The population of this research is all class V students, totaling 125 students. The sample from this research consisted of 10 students after being tested on a questionnaire who were included in the low communication skills category. This research uses a quantitative experimental approach (preexperimental), with a one group pretest-posttest design research design. Data collection methods in this research are observation, questionnaires and documentation. Data processing uses SPSS version 25 with Paired Test analysis. Based on the paired samples test table for the t count, it shows the number 6.021, with df = n-1 = 9 at the 5% significance level, we get t table = 1.833. Which means 6.021 > 1.833. This shows that providing sociodrama techniques has an effect on improving the communication skills of class V students at SDIT Al-Uswah Banyuwangi